Optical, Wired and Wireless Multimedia Service Access Solutions for Trend Setting Real Estates - Peter Mandl; P. Schrotter; E. Leitgeb (Communications - Scientific letters of the University of Zilina, 2008)
It is a well known fact that the value of real estates is raised tremendously by its connection to information technology services like Voice over IP (VoIP), IPTV, Video on Demand (VoD), basic Internet services and house-, security- and surveillance technologies. This paper will focus on different state of art methods to connect a real estate to the above mentioned services and will also discuss various inhouse cabling systems and related devices. Advantages and disadvantages between the miscellaneous combinations will be discussed.